PENGARUH KETEBALAN DI TENGAH TABUNG MOTOR ROKET RX 122 YANG PANJANG (THE EFFECT OF THICKNESS IN THE MIDDLE OF RX 122 LONG ROCKET MOTOR TUBE) - nFN ediwan (National Institute of Aeronautics and Space - LAPAN, 2017)
In the calculation of rocket tube due to the effect of pressure and temperature, if the comparison of length and diameter is large, then the bending stress and bucking stress will occur because of the weight, shear force, and torsion of the tube. For this reason, the tube needs to be thickened on the middle part so the pressure in the middle part will be reduced but will not result a new bigger pressure. In-depth analysis of the tubes was conducted on a long tube which is 2000 mm long and having 122 mm diameter. The analysis was only regarding the effect of the pressure on the tube with same thickness and the tube with thickened middle part for the purpose of seeing the effect of thickening the middle part of the tube and how much thickness in the middle part is allowed, so the effect of bending and buckling stress can be neglected. AbstrakPada perhitungan tabung roket akibat pengaruh tekanan dan temperatur, bila perbandingan antara panjang dan diameter cukup besar, perlu memperhitungkan terjadinya tegangan bending akibat berat dan tegangan buckling akibat ketebalan. Untuk menghindari tegangan tersebut maka bagian tengah tabung harus lebih tebal agar tegangan bagian tengah berkurang, tetapi tidak menimbulkan tegangan yang lebih besar lagi. Analisis yang lebih mendalam tentang tabung dilakukan pada tabung yang cukup panjang yaitu 2000 mm dan diameter 122 mm. Analisis yang dilakukan hanya dari pengaruh tekanan saja pada tabung yang tebalnya sama dan tabung yang tengahnya dipertebal, dengan tujuan untuk melihat pengaruh penebalan bagian tengah tabung tersebut dan sampai ketebalan berapa tabung bagian tengah diizinkan sehingga akibat terjadinya bending dan buckling dapat diabaikan.